Cardiac Manifestations in COVID-19 Patients: A Focus on the Pediatric Population. (17th July 2021) - Abi Nassif, Tania; Fakhri, Ghina; Younis, Nour K.; Zareef, Rana; Al Amin, Farah; Bitar, Fadi; Arabi, Mariam
Abstract : Background . SARS-CoV-2 is a new strain of the coronavirus family that emerged by the end of 2019 and led to the unpreceded COVID-19 pandemic. The virus affects multiple organs simultaneously and leads to a high rate of morbidity and mortality in all age groups. The cardiovascular system is one of the major affected organ systems. Various mechanisms including direct myocardial injury contribute to the cardiac manifestations of COVID-19 patients. Methods . We performed a comprehensive and updated search on the cardiac manifestations of COVID-19. Our search included laboratory and imaging evaluations. In addition, we added a unique section on the effect of SARS-CoV-2 on the cardiovascular system in the pediatric population. Results . COVID-19 might have an effect on the cardiovascular system at various levels leading to myocardial ischemia, arrhythmia, heart failure, myocarditis, and multisystem inflammatory syndrome in children. The incidence of cardiovascular complications varies among patients. This paper also provides a comprehensive summary of all the reported pediatric cases with cardiac manifestations. Conclusion . Multidisciplinary teams are crucial for adequate management of patients with COVID-19 regardless of age. Timely diagnosis is critical in reducing mortality.